REGARDING COMPLEX SENTENCES IN ANCIENT CHINESE AND SOME IMPLICATIONS FOR THE TRANSLATION INTO VIETNAMESE (Journal of Foreign Language Studies, 2020)
One-syllable words and simple sentences are often used in Ancient Chinese. Despite being rarely used, complex sentences contain many contents related to words, phrases, simple sentence and forms of sentences. This article provides implications for translating ancient Chinese complex sentences into Vietnamese based on the analysis of their forms and features. It is hoped to improve the quality and effectiveness of the translation of ancient Chinese, thus, facilitate leaners’ exploration of ancient Chinese.
Keywords: complex sentence; features; translation of ancient Chinese